(untitled) (TECHNICAL SCIENCE RESEARCH IN UZBEKISTAN, 2024)
This article talks about the management of organizational change and is a guide for students of the direction of the establishment of cultural and art institutions and management. An organization is a systematized, conscious Association of people who mobilize to achieve certain goals in terms of socio-economic production, as well as provide for the achievement of managerial tasks. One of the peculiarities of the management process itself lies in the fact that various organizational changes are carried out when socio-political processes change, positive and negative effects on the requirements of the market economy, changes in leaders and similar vital necessities arise.